ZupT Is a Zn(II) Uptake System in Escherichia coli - Grass, Gregor (American Society for Microbiology, 2002)
Escherichia coli zupT (ygiE), encoding a ZIP family member, mediated zinc uptake. Growth of cells disrupted in both zupT and the znuABC operon was inhibited by EDTA at a much lower concentration than a single mutant or the wild type. Cells expressing ZupT from a plasmid exhibited increased uptake of (65)Zn(2+).